Artificial Intelligence (AI) Chatbots and Customer Experience : Developing a Comprehensive Understanding Through Analysis of Existing Literatures - Karmakar, Subrata (My University, 2024)
There has been a substantial rise in academic interest in AI chatbots and studies on customer experience over the past decade. Nevertheless, regardless of its significance, there has been a lack of thorough evaluations, resulting in fragmented research and an absence of a holistic understanding of the complex dynamics between AI chatbots and customer experience. This study employs the Theory-Context-Characteristics-Methods (TCCM) review framework to systematically analyze 52 articles to identify the prevailing theories, contexts (industries and countries), characteristics (key variables and relationships), and methods (research approaches and analysis techniques) used in AI chatbot and customer experience research. The researcher identifies gaps in the current literature and suggests future research directions. These include prioritizing conceptual investigations to strengthen theoretical foundations, examining how cultural contexts affect chatbot interactions, studying the long-term effects on customer attitudes, and addressing the ethical implications of using AI chatbots. Furthermore, the study indicates the necessity for additional qualitative studies in order to achieve a more balanced perspective. This study enhances the AI chatbot and customer experience sectors by integrating existing studies, providing a thorough review, and giving theoretical and managerial implications.
Keywords: Customer experience, chatbot, literature review, TCCM framework